Pelayanan Kesehatan Hewan (Aktif Service) di Kota Parepare - Nurul Amin; Muh Imran; Dwi Ekawati Rustan; Putri Andry; Siti Nurhidayah; Jumaidil Jumaidil (Gapenas Publisher, 2022)
Actif service (supervision, medicinal, and record of animal desease) held in every region in Parepare City through internship activities in Dinas Pertanian, Kelautan dan Perikanan in Parepare City. The method which applied is active service and passive service of the society. The target of animal active service is livestok of society, livestock groups, partnership, and beloverd animals. The kind of activities which held is provide animal health implementation services in preventive, observation, diagnosis, treatment, health recovery, and rehabilitation